1992
DOI: 10.1111/j.1530-0277.1992.tb00702.x
|View full text |Cite
|
Sign up to set email alerts
|

Brain Gray and White Matter Volume Loss Accelerates with Aging in Chronic Alcoholics: A Quantitative MRI Study

Abstract: Magnetic resonance imaging (MRI) was used to study in vivo the brains of 49 patients with chronic alcoholism, 3 to 4 weeks post-withdrawal, and 43 normal healthy controls, all right-handed male veterans between the ages of 23 and 70 years. MRI scans were analyzed using a semi-automated procedure, which allowed the subcortical regions to be segmented into cerebrospinal fluid (CSF) and brain tissue and the cortical regions to be segmented into CSF, gray matter, and white matter. An age regression model was used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

21
361
4
17

Year Published

1993
1993
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 529 publications
(403 citation statements)
references
References 36 publications
21
361
4
17
Order By: Relevance
“…7,8 CT and MRI observations of reduced white matter volumes in alcoholics 2,3 have been confirmed by quantitative pathological studies. 9 In a volumetric study, Kril et al 10 demonstrated a negative correlation between white matter volume and maximum daily alcohol intake.…”
Section: Introductionmentioning
confidence: 65%
See 2 more Smart Citations
“…7,8 CT and MRI observations of reduced white matter volumes in alcoholics 2,3 have been confirmed by quantitative pathological studies. 9 In a volumetric study, Kril et al 10 demonstrated a negative correlation between white matter volume and maximum daily alcohol intake.…”
Section: Introductionmentioning
confidence: 65%
“…Proteomics of human alcoholic prefrontal cortex K Alexander-Kaufman et al alcoholics. 2,3,[9][10][11] A general decline in the expression of differentially expressed proteins was documented in alcoholic brains. Average PMIs for both alcoholic groups were longer than the control group and this may suggest some post-mortem degradation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In subjects with severe alcohol-dependence, computed tomography (CT), and magnetic resonance imaging (MRI) studies have consistently shown reduced gray and white matter volumes, with marked losses in the frontal lobes, the medial temporal, and parietal cortices, in subcortical structures (thalamus, caudate, and lenticularis nuclei) and in the cerebellar cortex (Brewer and Perrett, 1971;Jernigan et al, 1991;Pfefferbaum et al, 1992;Shear et al, 1996;Sullivan, 2003a;Sullivan et al, 2003b). Thinning of the corpus callosum , reduced volume in the pons (Sullivan et al, 2003b) and in the cerebellar vermis were also reported.…”
Section: Introductionmentioning
confidence: 98%
“…Although there is a substantial literature regarding its incidence on structural brain damage (eg Fein et al, 2002;Hommer et al, 2001;Pfefferbaum et al, 1992) and neuropsychological function (Parsons and Nixon, 1998;Oscar-Berman et al, 1997) in detoxified alcohol-dependents, no study has explored its consequences in alcoholdependents with preserved psychosocial functioning.…”
Section: Introductionmentioning
confidence: 99%